User misrepresentation in online social networks: how competition and altruism impact online disclosure behaviours. Issue 12 (1st December 2020) - Church, Mitchell; Thambusamy, Ravi; Nemati, Hamid
ABSTRACT: Their sheer size and scale give social networks significant potential for shaping popular opinions. While the spread of information and influence within social networks has been popular area of research for some time, more recently a research trend has appeared in which the researcher seeks to understand how users can aggressively influence community opinions, often using misrepresented or false information. Such misrepresentations by users are deeply troubling for any social network, where revenue-generation and their reputation depend on accurate and reliable user generated information. This study investigates the individual motivations that both promote and inhibit intentions towards personal information misrepresentation. These motivations are hypothesised to result from the dichotomy of competitive and altruistic attitudes existing with social network communities. Results of a survey analysis involving 502 users of Facebook offer insights useful for understanding social network information sharing practices. Marketing strategies, in particular, should benefit from the careful evaluation of the factors that lead to honesty (or dishonesty) among OSN users.